O transporte metropolitano de passageiros na região metropolitana de Fortaleza: o caso de Horizonte – Pacajus - Sampaio, Cleiber Sousa (2021)
This dissertation aims to discuss the role of the metropolitan passenger transport system in the Metropolitan Region of Fortaleza (RMF), especially between the cities of Fortaleza, Horizonte and Pacajus. To this end, I try to figure out the dynamics of flows and their demand in the South-Southeast region of the RMF. Due to the public policies of fiscal incentive of the government of the state of Ceará and the availability of cheap labor as a result of the implantation of industries on the margins of the BR-116 highway, the passenger flows between the metropolis and these municipalities intensify. In addition to activities that are related to commute to work and to carry out activities to purchase products, education and health services also motivate population mobility. Economic activities and the supply of goods and services explain, in part, the greater integration of the municipalities of Horizonte and Pacajus with the metropolis of Fortaleza. The road infrastructure and the transport system contribute to this dynamism, highlighting, in this area, the performance of the São Benedito Auto Via metropolitan bus company and the complementary transport cooperatives Cooperativa dos Drivers de Transporte Alternativo de Pacajus Ltda. (COTRALP), the Complementary Transport Cooperative of Horizonte (COOTACHE) and the Alternative Transport Cooperative of the Municipality of Horizonte (COOTAMH), responsible for guaranteeing the commuting in that region. Data surveys were carried out. Metropolitan integration has been required investments in the region's road system and public transport, which concerns the need for new means of transportations for serving the population in this area. However, what is observed is the increasingly use of private transport more than public passenger transport.